Antioxidant Activities of the Rhizomes of different Zingiberaceae Plants of North-East India - Ningombam, Swapana; Nahakpam, Lokendrajit; Laitonjam, Warjeet S.; Singh, C.B. (Asian Journal of Biological and Life Sciences, 2013)
In the present investigation, different fractions of rhizomes different plants of Zingiberaceae family were tested for their in vitro anti-oxidant activities. Protocols such as 2, 2-diphenyl-1-picrylhydrazyl (DPPH) methods and β-carotene-linoleic acid methods have been used for evaluation. The antioxidant activities of the extracts of the rhizomes in different solvents like methanol, chloroform and petroleum ether were reported. All the different solvent extracts of each plant shows different absorbance values indicating their bioactive contents. The study reveals that the highest activity of anti¬oxidant was observed in methanol extract in some plants while high activity (anti-oxidant) was observed in Chloroform extract in some plants.